DISCUS AQUARIUM WATER QUALITY ANALYSIS USING THE METHOD FUZZY MAMDANI - Ronald Belferik; Micka Krisdayani br Manurung (Lembaga Pengembangan Kinerja Dosen, 2022)
Aquarium is one of the media that is often used as a habitat for various types of animals that live both on land and in water. Many beautiful fish in the scenery are placed in aquariums filled with water as decorations. However, to place fish whose natural habitat is in vast water into an aquarium must require knowledge of the water quality that is suitable for these fish. Clear water is not necessarily suitable for the living conditions of fish. Fish that live in an open water environment grow well because not only is there sufficient food but there is an exchange of matter and energy such as oxygen, carbon dioxide and salts. Whereas in an aquarium environment, as a closed system, sudden and drastic changes to water parameters often occur (such as temperature, ph and ammonia content), which will cause fish stress and often lead to death. Therefore, the knowledge and ability to determine good fish aquarium water quality is an important element for fish keepers, especially hobbyists of ornamental fish such as discus. Classifying quality with a crisp set is a common practice. The number of variables involved in the aquarium (in this case, the object of research is discus) causes determination with a firm (crisp) set to be less appropriate. Therefore, the fuzzy mamdani method will produce outputs that are more suitable for analyzing the quality of aquarium discus. The input variables are density, temperature, and acidity. The outputs used are